History and photojournalism: reflections on the concept and research in the area (Revista Tempo e Argumento, 2016)
AbstractThis article aims to think through historical research with press photography and photojournalism in the 1970-80s in Brazil by means of some reflection axes: the photographic image statute, the concept of photojournalism, the construction of a specific photojournalistic language on the pages of the media, the temporality of production and consumption of the various types of press photography, the forms of image circulation and reception. Keywords: Photojournalism; Photography; History and press. Original title: História e Fotojornalismo: reflexões sobre o conceito e a pesquisa na área.